The origins of the modern hygiene in Bari: In memory of Enea Grosso - Riformato, Giacomo; Noviello, Chiara; Cuscianna, Eustachio; Barbuti, Giovanna; Tafuri, Silvio (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Professor Enea Grosso, a distinguished Italian scholar in Public Health, made significant contributions during his tenure at the University of Milan, Camerino and in particular Bari, expanding the discipline’s research horizons. Born in Milan in 1922, Grosso’s career included collaborations with renowned scientists like Albert Sabin. Notable achievements include his innovative response to the 1973 cholera epidemic in Apulia and his promotion of mathematical models in epidemiology. Grosso passed away unexpectedly in 1984, leaving a lasting impact on the scientific community.